1993
DOI: 10.1088/0031-9155/38/4/002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the optical properties of the skull in the wavelength range 650-950 nm

Abstract: The optical properties of samples of bone from pig skull have been measured over the wavelength range 650-950 nm. The scattering phase function was measured on thin samples of the bone using a goniometer, and a value for the mean cosine g, of the scattering angle, was calculated. The scattering and absorption coefficients, mu s and mu a were then determined from measurements of diffuse reflectance and transmittance made with a pair of integrating spheres, by a step-wise search through a table of diffuse reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(157 citation statements)
references
References 22 publications
11
143
1
2
Order By: Relevance
“…The attenuation coefficients calculated in this study were lower than the equivalent attenuation coefficients of skulls [44,45] and skin [46,47] reported in previous studies. The discrepancies may be attributed to the difference in experimental design including selection of light source and detector, experimental setup, and the materials and sample preparation.…”
Section: Discussioncontrasting
confidence: 88%
“…The attenuation coefficients calculated in this study were lower than the equivalent attenuation coefficients of skulls [44,45] and skin [46,47] reported in previous studies. The discrepancies may be attributed to the difference in experimental design including selection of light source and detector, experimental setup, and the materials and sample preparation.…”
Section: Discussioncontrasting
confidence: 88%
“…In literature there are studies reporting on ex-vivo or post-mortem measurements for the characterization of the human head optical properties, [15][16][17][18][19][20] but they are not representative of an in-vivo condition.…”
Section: Introductionmentioning
confidence: 99%
“…Jagdeo et al [40] showed that this radiation range can penetrate soft tissues, bone, and brain parenchyma in a study using cadavers preserved in formalin. According Firbank et al [41], the absorption coefficient of radiation in the 650 nm and 950 nm range is between 0.02 and 0.05 mm -1 in the skull, while the scattering coefficient has a linear decrease from 35 mm -1 at 650 nm wavelength to 25 mm -1 at 950 nm wavelength. Similarly, the absorption and scattering coefficients of brain white and gray matter for the same region of the spectrum do not differ greatly [42].…”
Section: Tclt Radiation Transmission In the Skullmentioning
confidence: 99%